2015
DOI: 10.1108/k-06-2014-0117
|View full text |Cite
|
Sign up to set email alerts
|

Durable product review mining for customer segmentation

Abstract: Purpose -More and more e-commerce web sites are using online customer reviews (OCRs) for customer segmentation. However, for durable products, customer purchases, and reviews only once for a long time, as while the product review score may highly affected by service factors or be "gently" evaluated. Existing regression or machine learning-based methods suffer from low accuracy when applied to the OCRs of durable products on e-commerce web sites. The purpose of this paper is to propose a new approach for custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Sentiment analysis, also called opinions mining, is used for analyzing people’s opinions towards products or services (Liu, 2010). There are many applications, for example, Jiang et al (2015) conducted customer segment analysis base on online customer reviews of durable products. Typical tasks of sentiment analysis are: finding suitable collection of reviews, pre-processing texts by using natural language processing techniques and identifying sentiment in texts (Schmunk et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sentiment analysis, also called opinions mining, is used for analyzing people’s opinions towards products or services (Liu, 2010). There are many applications, for example, Jiang et al (2015) conducted customer segment analysis base on online customer reviews of durable products. Typical tasks of sentiment analysis are: finding suitable collection of reviews, pre-processing texts by using natural language processing techniques and identifying sentiment in texts (Schmunk et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sentiment analysis and bidirectional recurrent neural network (RNN) were applied in the analysis of customer reviews [5,9]. Latent class analysis can better explain the characteristics of the online customer reviews data of durable products for customer segmentation, which may provide support for new product design and development, repositioning of existing products, and product differentiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation by Duan, et al found that 20 per cent of consumers ranked products based on online ratings alone when searching for product information on an e-commerce website (Duan et al , 2009). In addition, numerous existing studies have shown that online ratings or online reviews play an important role in the decision-making process of consumers, which are not only sources of information used by consumers to understand the function and quality of a product or service but also sources of information used to find desirable products (Fang et al , 2016; Jiang et al , 2015; Zhou et al , 2015; Sameti et al , 2016; Salehan and Kim, 2016). When a consumer is willing to buy an expensive product, such as mobile phone and automobile, he (she) usually considers several alternative products and their attributes according to his (her) expectations, as well as to the corresponding online ratings.…”
Section: Introductionmentioning
confidence: 99%